1970
DOI: 10.1063/1.1673312
|View full text |Cite
|
Sign up to set email alerts
|

Exact Finite Method of Lattice Statistics. IV. Square Well Lattice Gas

Abstract: The temperature-dependent phase equilibrium of simple classical molecules has been studied, using a model based on the two-dimensional square lattice. The intermolecular potential includes a hard core extending to the first-neighbor distance and a finite interaction (attractive or repulsive) at the second-neighbor distance. The transfer matrix method of calculation is used for lattices of infinite length and finite circumference up to 16 sites. At all temperatures studied there is a single phase transition, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…• The matrix method of Kramers and Wannier [17][18][19][20][21][22][23][24][25][26][27][28][29][30], • The density (or activity) series expansion [15,22,[31][32][33][34][35], • The generalized Bethe method [33,[36][37][38][39][40][41], • The Rushbrooke and Scoins method [42],…”
Section: Introductionmentioning
confidence: 99%
“…• The matrix method of Kramers and Wannier [17][18][19][20][21][22][23][24][25][26][27][28][29][30], • The density (or activity) series expansion [15,22,[31][32][33][34][35], • The generalized Bethe method [33,[36][37][38][39][40][41], • The Rushbrooke and Scoins method [42],…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition to L the second independent intensive variable is the activity Z= exp (/-L/kT The pressure is a zeroth-order property given by the dominant eigenvalue /.. of the transfer matrix, while the densities should be regarded as first-order properties since they are expectation values of appropriate operators over the eigenvector belonging to A. s New features appearing in the present problem arise primarily from the increased range of the potential (to third-neighbor distances).…”
Section: Methodsmentioning
confidence: 99%
“…In these models, occupancy in the first shell, second shell, and, in some cases, even more distant shells is forbidden. Different types of potential functions also have been considered, including hard spheres [46], square well potentials [47], and repulsions with large positive (but not infinite) energies [48,49]. It has been shown that models with first-neighbor exclusions give second-order phase transitions [50], but models with larger exclusion shells can give a first-order transition [51][52][53].…”
Section: Systems With Order -Disorder Transitionsmentioning
confidence: 99%
“…Consider equations (36) and (37) as linear approximations for an expansion of the configurational energy in powers of density. Then, the series ... ) ( ) ( Using equations (47) and (48) instead of equations (36) and (37) and leaving only linear, quadratic, and cubic terms, we obtain instead of equation 41:…”
Section: Improving Functions F 3 (X B T) and F 2 (X 1 T)mentioning
confidence: 99%
See 1 more Smart Citation